PENINGKATAN MINAT BELAJAR SISWA KELAS III DALAM PEMBELAJARAN BAHASA INDONESIA MELALUI PENGGUNAAN MEDIA AUDIO VISUAL DI SD MUHAMMADIYAH 10 TALLO KOTA MAKASSAR - Lutfiyanti, Fadilah; Agus, M; Ulviani, Maria (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this study is to describe the increase in students' interest in learning Indonesian through the use of audio-visual media in grade III at Muhammadiyah 10 Tallo Elementary School, Makassar City. This type of research is Classroom Action Research (CAR) which is carried out in two cycles, each cycle consisting of planning, implementation, observation, and reflection stages. The research subjects were 23 grade III students of Muhammadiyah 10 Tallo Elementary School. Data collection techniques through observation, interviews and student learning interest questionnaires compiled based on indicators of students' feelings of pleasure, involvement, interest, and attention. Data were analyzed using quantitative and qualitative analysis techniques. Based on the results of the research and discussion that have been presented in the previous section, it is concluded that the use of audio-visual media can increase the interest in learning grade III students in learning Indonesian at Muhammadiyah 10 Tallo Elementary School. This result is shown by the results of the research on the percentage of student learning interest classically in Cycle I reaching 73.9% with a sufficient/good category, but does not meet the criteria for success. The results of the reflection on Cycle I, carried out in Cycle II, included increasing teacher supervision during learning, including a question and answer session after the video screening to increase student focus, and replacing animated videos with more attractive displays with less text to suit the characteristics of third-grade students. As a result, the results of the student learning interest questionnaire increased to 82.6%, with a good category and having achieved a completeness score. Thus, the application of audio-visual media in Indonesian language learning can increase the learning interest of third-grade students, marked by an increase in aspects of feelings of pleasure, interest, attention, and student involvement in the learning process.